Insulin Resistance in Alzheimer's Disease - Ferreira, Laís S. S.; Fernandes, Caroline S.; Vieira, Marcelo N. N.; De Felice, Fernanda G. (Frontiers in Neuroscience, 2018)
The epidemiological connection between diabetes, obesity and dementia represents an important public health challenge but also an opportunity to further understand these conditions. The key intersection among the three diseases is insulin resistance, which has been classically described to occur in peripheral tissues in diabetes and obesity, and has recently been shown to develop in Alzheimer’s disease brains. Here we review encouraging preclinical and clinical data indicating the potential of targeting impaired insulin signaling with antidiabetic drugs to treat dementia. We further discuss biological mechanisms through which peripheral metabolic dysregulation may lead to brain malfunction, providing possible explanations for the connection between diabetes, obesity and Alzheimer’s disease. Finally, we briefly discuss how lifelong allostatic load may interact with aging to increase the risk of dementia in late life.